The Influence Of Islamic Digital Media and Value Literacy on Social Media Ethics among Twelfth-Grade Students at MAN 2 Kota Probolinggo - Muhammad 'Affan Haydar Haydar; Muhammad Alfi Syahrin (Educational Research Center, 2026)
This study examines the influence of Islamic digital media and value literacy on social media ethics among twelfth-grade students at MAN 2 Kota Probolinggo. Using a quantitative correlational survey, data were collected from all 32 students via a validated Likert-scale questionnaire. Multiple regression with robust HC3 standard errors showed that Islamic digital media had no significant effect on social media ethics (β = -0.0007; p = 0.9965), whereas value literacy demonstrated a significant positive influence (β = 0.709; p < 0.01). Together, both variables significantly predicted social media ethics (F = 10.602; p < 0.01), with an R² of 0.502, meaning 50.2% of the variance was explained. These findings underscore that value literacy plays a crucial role in fostering students' ethical conduct in digital environments.